Comparison of different cytological parameters of three species of Ocimum (Bangladesh Journal of Botany, 2020)
Karyomorphological analysis of three species of the genus Ocimum (O. basilicum L., O. americanum L. and O. tenuiflorum L.) was carried out. Gross chromosome morphology of these species are nearly sub metacentric (Sm), nearly metacentric (m) and metacentric (M) in nature. The high values of mean chromosome length, total chromosome length of O. americanum followed by O. basilicum show their primitiveness. Whereas, lower values of these parameters in O. tenuiflorum denotes evolved nature of the species. All the three species of Ocimum showed high values of total forma percentage (TF%) in conjunction with low coefficient of variation (CV), which corresponds to the primitive status in the evolution of flowering plants and was placed in 3A class of Stebbins’ system, indicating the presence of symmetrical karyotype in them. Karyotyping along with UPGMA based dendrogram analysis clearly separated O. basilicum L. and O. americanum L. in one cluster and O. tenuiflorum L. in a separate cluster with greater Euclidian distance.